A Systematic Review of Social Capital and Resilience in the Post-COVID Era: Implications for Sustainability - Fatin, Tasnia; Wahab, Sazali Abd (Pakistan Journal of Humanities and Social Sciences, 2025)
The COVID-19 pandemic has profoundly altered the dynamics of social capital, including trust, networks, and collaborative action within communities. Lockdowns, social distancing protocols, and disruptions to conventional engagement modes significantly impacted these elements, particularly among marginalized populations. This review analyzes the evolving role of social capital in fostering resilience, cohesion, and sustainable recovery in the post-COVID era. Employing a systematic literature review, peer-reviewed journal articles, book chapters, and reputable reports published pre- and post-pandemic were selected through Scopus, Web of Science, and Google Scholar. Inclusion criteria prioritized empirical and theoretical insights relevant to post-pandemic contexts. Core dimensions of social capital—trust, reciprocity, and connectedness—have faced challenges, such as erosion of trust and digital inequality. However, digital platforms enabled new modes of engagement and trust-building. Thematic synthesis revealed dual aspects of social capital in recovery—both obstacles and opportunities. Social capital is critical in advancing community resilience and sustainable development. Digital inclusion, equitable engagement, and community-based programs must be prioritized. A conceptual framework is proposed linking social capital dimensions to post-pandemic recovery and environmental resilience.